2012
DOI: 10.1002/pmh.1216
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality disorder in suicidal adolescents

Abstract: The diagnosis of Borderline Personality Disorder (BPD) in adolescents has been controversial. Thus, few studies have examined BPD in suicidal adolescents, even though it is strongly associated with suicidal behaviors in adults. This study examines differences between suicidal adolescents with (n=47) and without (n=72) BPD on history and characteristics of suicidal behavior, Axis I comorbidity, affect regulation, and aggression. Assessments were completed with both adolescents and parents, and consensus ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 51 publications
1
34
1
Order By: Relevance
“…Other reports based on this sample have been published elsewhere (Selby, & Yen, 2014; Yen, Fuller, Solomon, & Spirito, 2014; Yen, Gagnon, & Spirito, 2013; Yen, Kuehn, et al, in press; Yen et al, 2012). The present study differs from those studies in that here we examine predictors of NSSI using the Functional Assessment of Self-Mutilation (FASM).…”
Section: Methodsmentioning
confidence: 91%
“…Other reports based on this sample have been published elsewhere (Selby, & Yen, 2014; Yen, Fuller, Solomon, & Spirito, 2014; Yen, Gagnon, & Spirito, 2013; Yen, Kuehn, et al, in press; Yen et al, 2012). The present study differs from those studies in that here we examine predictors of NSSI using the Functional Assessment of Self-Mutilation (FASM).…”
Section: Methodsmentioning
confidence: 91%
“…However, personality traits have been shown repeatedly to be the strongest variables related to suicidality, and an extensive review showed that PDs, based on DSM classifications, place individuals at significantly greater risk for suicide . Cluster B PD, especially borderline PD, was identified as the strongest risk factor for suicide attempts . Moreover, other PDs have been shown to increase the risk for new suicidal attempts; these include depressive, avoidant, schizotypal disorders, and schizoid PD .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature examining the stability of adolescent BPD over time has concluded that it is modest to low, ranging from 9%, in a mixed clinical sample, to 29% in an adolescent inpatient sample (Arens et al, 2013;Bernstein et al, 1993;Garnet, Levy, Mattanah, Edell, & McGlashan, 1994;Gunderson, Stout, McGlashan et al, 2011;Meijer, Goedhart, & Treffers, 1998;Mattanah, Becker, Levy, Edell, & McGlashan, 1995;Yen, Gagnon, & Spirito, 2013).…”
Section: Stability Of Adolescent Bpdmentioning
confidence: 99%